Kinetics of electric arc furnace slag leaching in alkaline solutions. (1st April 2016) - Nikolić, Irena; Drinčić, Ana; Djurović, Dijana; Karanović, Ljiljana; Radmilović, Vuk V.; Radmilović, Velimir R.
Highlights: The leaching of Al and Si from steel slag in alkaline solutions was investigated. Leaching is controlled by the bulk diffusion through the product layer crystals. CASH gel is reaction product of slag leaching in alkaline environment. Choice of alkali solution greatly influences the Si and Al dissolution. Abstract: The dissolution of electric arc furnace steel slag (EAFSS) in highly alkaline MOH solution (M = alkali metal Na or K) has been investigated with emphases on the influence of the initial alkali concentration, solid to liquid (S/L) ratio and temperature on the kinetics of Si and Al dissolution from EAFSS. The shrinking core model (SCM) was used to analyze experimental data and the results have shown that the Si and Al dissolution from EAFSS was greatly influenced by MOH concentration, alkaline ion type and temperature. The dissolution process was controlled by the bulk diffusion through the product layer crystals. The activation energy for Si and Al dissolution was 55.27 kJ/mol and 48.05 kJ/mol in NaOH solution and 90.68 kJ/mol and 33.62 kJ/mol in KOH solution, respectively.